The Role of School Principals and Teachers in Maximized Education Quality in The Era of Independent Learning in Achieving Indonesia's Vision 2045 - Riska Hartanti; Anam Sutopo; Sofyan Anif (Journal of Educational Sciences, 2026)
This study examines the collaborative role of school principals and teachers in managing educational quality within the Merdeka Belajar era as a strategic effort to achieve the Golden Indonesia 2045 Vision. Using a qualitative literature study approach, the findings reveal that the effective implementation of the Merdeka Curriculum is strongly influenced by the synergy between principals’ collaborative instructional leadership and teachers’ pedagogical autonomy. Principals function as facilitators who promote continuous professional development, encourage reflective instructional practices, and optimize the use of assessment data to enhance learning outcomes, while teachers design differentiated, student-centered learning that strengthens the Pancasila Student Profile. The analysis also highlights that alignment across planning, implementation, and evaluation particularly through the development of a data-driven Education Unit Operational Curriculum (KOSP) serves as a strategic bridge connecting national educational policies to classroom practices, thereby ensuring consistency in quality improvement efforts. Despite these positive developments, the study identifies persistent challenges such as limited resources, uneven digital readiness, and administrative burdens that may hinder optimal collaboration. Overall, the study confirms that sustainable, participatory, and innovation-oriented quality management is essential for developing superior human resources capable of supporting Indonesia’s long-term national aspirations toward 2045.